Inter-departmental Collaboration to Enhance Programs and Meet Community Needs - Gale B. Rice PhD.,CCC-SLP; Mary Beth Ohlms M.Ed.; Carmen Russell PhD.CCC-SLP; Jamie VanDycke PhD. (Academic Chairpersons Conference Proceedings, 2016)
This interactive session will describe how three academic departments shared their resources and expertise to enhance program quality by giving their students opportunities to collaborate with both faculty and students of different disciplines while meeting the needs of under-represented community groups in a camp context.
Keywords: collaboration; mission; interdisciplinary; community; curriculum